Dietary Beliefs in Children and Adolescents with Inflammatory Bowel Disease and their Parents. Issue 3 (16th June 2022) - Bramuzzo, Matteo; Grazian, Federica; Grigoletto, Veronica; Daidone, Alessandro; Martelossi, Stefano; Mario, Federica; Maurel, Eleonora; Lega, Sara; Giudici, Fabiola; Di Leo, Grazia; Barbi, Egidio
Abstract : Objectives: Patients with inflammatory bowel disease (IBD) may have diet-related beliefs that lead to restrictive dietary behaviours. This study aimed to evaluate dietary beliefs in young patients with IBD and their parents and the presence of restrictive behaviours. Methods: A questionnaire regarding dietary beliefs was administered to IBD patients aged 8-17 years and their parents. A Food Frequency Questionnaire was administered to patients with IBD and a peer control group. Results: Seventy-five patients and 105 parents were interviewed. Twenty-seven (36%) patients and 39 (37.1%) parents believed that dietary modifications could control the IBD course. Twenty-five (33.0%) patients and 33 (33.0%) parents believe that some dietary components can prevent relapse or improve symptoms (mainly abdominal pain and diarrhoea), while 36 (48%) patients and 60 (60.0%) parents believe that some foods can induce or worsen symptoms during an IBD flare. Patients believe that milk, dairy, fried and spicy foods, sweets and carbonated drinks could have a negative effect on IBD while fruits, vegetables and rice could have a positive impact. Parents believe that fruits and vegetables have a negative effect. Responses did not differ among patients classified according to IBD phenotype, activity status, or current therapies. Compared to controls, young patients with IBD have reduced daily consumption of milk, lunch meat, raw and cooked vegetables. Conclusions: About one-third of paediatric patients with IBD and their parents have dietary beliefs that lead to restrictive dietary behaviours.